2021
DOI: 10.3390/ijerph18115869
|View full text |Cite
|
Sign up to set email alerts
|

Baby Steps: Using Intervention Mapping to Develop a Sustainable Perinatal Physical Activity Healthcare Intervention

Abstract: While the benefits of physical activity (PA) during and after pregnancy have been established, many women do not reach the recommended PA levels during this time. A major barrier found in the literature is a lack of counselling by healthcare providers (HCPs), which is partly caused by the limited knowledge on the topic. The aim of this study was to develop an intervention to improve the promotion of PA by HCPs. We used Intervention Mapping (IM), a theory-based framework to develop an intervention, called “Baby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
0
7
0
3
Order By: Relevance
“…Even though some women indicated being eager to start being physically active again postpartum, they encountered biological barriers such as sufficient time needed to physically recover and to feel comfortable and safe to engage in PA again, which was also shown by others [35]. Healthcare providers should therefore be trained to give tailored, personalized advice on frequency, type, intensity and duration of PA and on how to limit SB, to help women and men towards realistic, feasible PA/SB goals [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though some women indicated being eager to start being physically active again postpartum, they encountered biological barriers such as sufficient time needed to physically recover and to feel comfortable and safe to engage in PA again, which was also shown by others [35]. Healthcare providers should therefore be trained to give tailored, personalized advice on frequency, type, intensity and duration of PA and on how to limit SB, to help women and men towards realistic, feasible PA/SB goals [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other research has described a lack of guidance and information from healthcare professionals as a barrier for a healthy lifestyle in a safe and effective way during the postpartum period [35]. While a trusted relationship with the healthcare provider and reliable, consistent advice are important, research has shown that healthcare providers often lack the knowledge, time and skills to give appropriate advice on lifestyle behaviors during pregnancy and postpartum [36]. This often results in limited or conflicted advice given [39].…”
Section: Discussionmentioning
confidence: 99%
“…A previous educational interventional study showed improvement in the professionals' knowledge regarding leisure-time walking and women who were cared for by the intervention group were more likely to receive guidance regarding leisure-time walking [45]. A recent study combining education about physical activity with a training session on facilitating behaviour change emphasised the importance of educating health professionals on prenatal physical activity based on the findings from a needs assessment that demonstrates health professionals had limited knowledge about physical activity during pregnancy [46], which is likely attributed to limited availability of undergraduate and continued professional training of healthcare professions on prenatal physical activity [47]. Thus, incorporating prenatal physical activity into the medical and nursing training schools would empower the healthcare providers with the knowledge and requisite skills they need to assist pregnant women in terms of prenatal physical activity prescription and advice.…”
Section: Discussionmentioning
confidence: 99%
“…Unabhängig vom Bewegungsniveau vor der Konzeption, reduzieren schwangere Frauen ihre körperliche Bewegung zugunsten sitzender Aktivitäten [6,8,10,21]. Der Prozentsatz der schwangeren Frauen, die die Empfehlungen für kA erreichen, liegt international bei etwa 20 % [2,5,8]. Darüber hinaus hat eine Pilotstudie in Deutschland gezeigt, dass das Niveau der kA vom Body-Mass-Index abhängt.…”
Section: Bedeutung Körperlicher Aktivität In Der Schwangerschaftunclassified
“…Gesundheitsfachkräfte, die Schwangere betreuen, sollten deshalb mit den internationalen Empfehlungen für Bewegung vertraut sein. Bisherige Studien zeigen eindeutig, dass diese Fachpersonen keine ausreichende Kenntnis über die Bewegungsempfehlungen und deren Vorteile haben und sie daher nicht genügend einbeziehen, wenn sie Frauen über einen gesunden Lebensstil informieren [5,20,25]. Hebammen haben eine zentrale Rolle bei der Bewegungsförderung in der Perinatalität, insbesondere bei Frauen mit Gewichtsproblemen [1,26].…”
Section: Bedeutung Körperlicher Aktivität In Der Schwangerschaftunclassified